Faili Kurds identity and integration controversy: Anthropology study in Wasit Governorate - Darab, Thanaa Abad ali Hadi; lbrahim, Thikraa AbdulAlmonem (Al-Adab Journal, 2021)
This study is a field study in the field of anthropology that took on importance in the nature of the search for identity controversy among a segment of Iraqi society, namely the Faili Kurds who live in the central and southern regions of Iraq. The study aims to reveal the reality of identifying the nature of the identity dialectic of the Faili Kurds according to the fact that it is the ethnic and national affiliation of this segment. Some of them:Faili Kurds are an integral part of Iraqi society, and they have a clear harmony in Iraqi society.The study showed that political loyalty would have had a great impact on their cultural reality. Dialect is the backbone of culture, and they are the result of interaction and adaptation with parties, forming a cultural structure in them Whereas, those who have political loyalty to the Kurdish parties tend to speak the Sorani dialect in addition to their Faili accent, as well as to the same extent of their affiliation with the Shiite parties who have a clear influence on the nature of speech and the language of communication.The results of the study show that they were subjected to the harshest forms of forced displacement by brutal and barbaric methods, and they were assaulted, their movable and immovable money plundered, their sons thrown in prisons, assaulted and absent from them to this day if they could not find them all under the pretext of dependency on Iran and this started. Operations from the beginning of the seventies to the end of the eighties.